Manajemen Keuangan Pendidikan Pada Masa Pandemi Covid – 19 di SMK Tamtama 2 Sidareja Kab. Cilacap - legowo, jhony; anjaya, warisno (Journal of Management Review, 2025)
During the Covid-19 Pandemic, which is currently being felt by almost all countries in the world, the problem of this pandemic of course has an impact on all aspects of life, especially in the world of education. As we all know, with the Covid-19 pandemic which has not yet ended, all activities related to the lives of many people have drastically decreased. Observing the world of education that is currently running, it really must be with sufficient strength to be able to compete and continue to exist. Strength in question is strength in terms of financing in an institution or educational institution. The cost of education is one of the important components in carrying out activities in schools. The principal of SMK Tamtama 2 Sidareja said that there are at least seven school components that must be managed properly in the context of school-based management, namely Curriculum Management and Teaching Programs, Management of Education Personnel, Student Management, Financial Management, Management of Educational Facilities, Management of Relationship Management. Of the various components, we will only focus on financial management during the Covid-19 pandemic at SMK Tamtama 2 Sidareja, Cilacap Regency.